x(x-2)=(x+2)

Simple and best practice solution for x(x-2)=(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-2)=(x+2) equation:


Simplifying
x(x + -2) = (x + 2)

Reorder the terms:
x(-2 + x) = (x + 2)
(-2 * x + x * x) = (x + 2)
(-2x + x2) = (x + 2)

Reorder the terms:
-2x + x2 = (2 + x)

Remove parenthesis around (2 + x)
-2x + x2 = 2 + x

Solving
-2x + x2 = 2 + x

Solving for variable 'x'.

Reorder the terms:
-2 + -2x + -1x + x2 = 2 + x + -2 + -1x

Combine like terms: -2x + -1x = -3x
-2 + -3x + x2 = 2 + x + -2 + -1x

Reorder the terms:
-2 + -3x + x2 = 2 + -2 + x + -1x

Combine like terms: 2 + -2 = 0
-2 + -3x + x2 = 0 + x + -1x
-2 + -3x + x2 = x + -1x

Combine like terms: x + -1x = 0
-2 + -3x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '2' to each side of the equation.
-2 + -3x + 2 + x2 = 0 + 2

Reorder the terms:
-2 + 2 + -3x + x2 = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -3x + x2 = 0 + 2
-3x + x2 = 0 + 2

Combine like terms: 0 + 2 = 2
-3x + x2 = 2

The x term is -3x.  Take half its coefficient (-1.5).
Square it (2.25) and add it to both sides.

Add '2.25' to each side of the equation.
-3x + 2.25 + x2 = 2 + 2.25

Reorder the terms:
2.25 + -3x + x2 = 2 + 2.25

Combine like terms: 2 + 2.25 = 4.25
2.25 + -3x + x2 = 4.25

Factor a perfect square on the left side:
(x + -1.5)(x + -1.5) = 4.25

Calculate the square root of the right side: 2.061552813

Break this problem into two subproblems by setting 
(x + -1.5) equal to 2.061552813 and -2.061552813.

Subproblem 1

x + -1.5 = 2.061552813 Simplifying x + -1.5 = 2.061552813 Reorder the terms: -1.5 + x = 2.061552813 Solving -1.5 + x = 2.061552813 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = 2.061552813 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = 2.061552813 + 1.5 x = 2.061552813 + 1.5 Combine like terms: 2.061552813 + 1.5 = 3.561552813 x = 3.561552813 Simplifying x = 3.561552813

Subproblem 2

x + -1.5 = -2.061552813 Simplifying x + -1.5 = -2.061552813 Reorder the terms: -1.5 + x = -2.061552813 Solving -1.5 + x = -2.061552813 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = -2.061552813 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = -2.061552813 + 1.5 x = -2.061552813 + 1.5 Combine like terms: -2.061552813 + 1.5 = -0.561552813 x = -0.561552813 Simplifying x = -0.561552813

Solution

The solution to the problem is based on the solutions from the subproblems. x = {3.561552813, -0.561552813}

See similar equations:

| 5x-13=4(2x-5) | | 5b+6-6b+2= | | 9x^2-32=40 | | 5.5q-4.6-6.6q=2.2-1.1q-2.4 | | 6.1x+3=5.1x | | 10(-2x+1)=-12(x+2)+34-8x | | 7x+9-8x+4=6x-7x-5 | | 7x+3=3+7x | | 7x+4y=18.25 | | 4(7x-2)+5(19-3x)=3(4x+3)-6 | | 2y+110+35=180 | | 5a+7=3a-15 | | 18x+4=58 | | (6x+7)-(4+5x)=12 | | (4*2k)+3k-2= | | 9+10r-2=9r+35-3r | | 48x^2+24x+3=0 | | x=-60+2s | | 2y+110+35=360 | | 3(x-1)-24=2(-1-x) | | 2w^2-3w-27=0 | | 4x+18=58 | | 2x+40=110 | | 10x+6=64 | | 3[3f+1]=7[2f+9] | | 3(5-4t)-t=18 | | 2[3e-7]=5[6-e] | | 3[2d-9]+5d=105 | | 40x+60(x-2)=380 | | 8c-4[c+3]=8 | | 41-32=r | | 7[5b+6]=-63 |

Equations solver categories